BUSINESS MODELS AND ACTIVITIES TOWARDSA CIRCULAR ECONOMY - Szajczyk, Marek (Management and Administration Journal, 2024)
The transition to a circular economy represents a fundamental shift in how businesses operate, one which involvesmoving away from the traditional linear model of “take, make, dispose” towards a system that prioritizes resource efficiency, waste reduction, and sustainable practices. The research presented here focuses on examining business models and activities that support the transition to a circular economy. It aims to identify and categorize business models aligned with circular economy principles; explore how companies implement circular practices and identify key challenges and enablers that impact businesses’ shift to circular practices. The findings unveil that there are two main approaches to resource circulations: the first involves slowing the resource flows and second involves closing resource loops. Moreover, the implementation practices at three levels: micro, meso and macro levels and four areas, production, consumption, waste management and development support were presented. The study probes the realm of circular economy within sustainability, unveiling its potential to make better use of finite resources, reduce emissions and boost economies. The conclusions of the paper emphasize that achieving a global circular economy model appears unrealistic.